Contributions to Nephrology 2006
DOI: 10.1159/000093598
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Peritoneal Dialysis in the Treatment of Uremia

Abstract: The real integration of a specific therapy into the renal replacement program is represented by the possibility of easy and free patient transfer from one treatment to another without restrictions. In the case of peritoneal dialysis we feel that its integration in the therapeutic approach of uremia represents an ethical obligation for the physician, a clinical opportunity for the patient and a good cost/benefit solution for care givers. A full conviction that peritoneal dialysis represents a real therapeutic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…With PD, holidays and travel are more flexible, because the individual is not confined to an area that has a renal unit. Potentially CAPD gives the patient more control over their own lives and should facilitate the chance of rehabilitation [53]. Some have suggested that individuals receiving PD are more likely to be employed than those on in-center HD [54,55].…”
Section: Quality Of Lifementioning
confidence: 99%
“…With PD, holidays and travel are more flexible, because the individual is not confined to an area that has a renal unit. Potentially CAPD gives the patient more control over their own lives and should facilitate the chance of rehabilitation [53]. Some have suggested that individuals receiving PD are more likely to be employed than those on in-center HD [54,55].…”
Section: Quality Of Lifementioning
confidence: 99%
“…Earlier reports on patient outcome of PD and HD gave conflicting results, ranging from favorable for HD over no difference to favorable for PD (4, 8, 10, 11, 13, 16-23). As pointed out by Port et al (21), correct interpretation of these studies is difficult because they differ in many aspects, such as type of statistical analysis (with or without correction for comorbidity, and presence of different factors of comorbidity), use of single center versus multicenter data, inclusion of incident or prevalent patients, and duration of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Anemia of chronic kidney diseases is a state of anemia caused by various factors that interfere with the production and metabolism of RBC [ 20 ]. Patients with uremia have significant toxin accumulation, and most of the toxins can be effectively removed by PD [ 21 ]. However, some of the medium and large molecules may remain and inhibit the function of renal erythropoietin [ 22 ].…”
Section: Discussionmentioning
confidence: 99%